Electronic modulation and surface reconstruction of cactus-like CoB2O4@FeOOH heterojunctions for synergistically triggering oxygen evolution reactions. Issue 21 (10th May 2022) - Yin, Xueli; Cai, Run; Dai, Xiaoping; Nie, Fei; Gan, Yonghao; Ye, Ying; Ren, Ziteng; Liu, Yujie; Wu, Baoqiang; Cao, Yihua; Zhang, Xin
Abstract : Cactus-like hierarchical CoB2 O4 @FeOOH/NF enables the fast mass transfer, abundant accessible active sites and strong synergism induced by Fe–B bond for optimizing electrical conductivity and the generation of CoOOH for triggering OER processes. Abstract : Cactus-like heterojunctions with FeOOH nanosheets wrapped on CoB2 O4 nanorods/nickel foam-(CoB2 O4 @FeOOH/NF) were fabricated by a hydrothermal and an electrodeposition strategy for OER processes. Benefiting from the cactus-like architecture for fast mass transfer and more accessible active sites, and strong synergistic effects induced by the formation of Fe–B bond for optimizing electrical conductivity, as well as facilitating the generation of CoOOH unveiled by in situ UV-vis measurement during the OER process, CoB2 O4 @FeOOH/NF shows superior OER performance with a low overpotential of 255 mV at 100 mA cm −2, and robust stability for 100 h at 100 mA cm −2 . The two-electrode alkaline electrolyzer (CoB2 O4 @FeOOH/NF||Pt/C/NF) using CoB2 O4 @FeOOH/NF as the anode requires a low cell voltage of 1.576 V at 100 mA cm −2 for driving water splitting, and maintains steadily for 125 h without attenuation at 300 mA cm −2 . This work provides insights into the roles of interfacial engineering by constructing heterojunctions of FeOOH and transition metal borate to design high-performance electrocatalysts for OERs.